Konsolidacja polskich przedsiębiorstw handlowych - Kałążna-Drewińska, Urszula (Consolidation of Polish Businesses, 2007)
Contents of the article comprise the following issues: 1. Changes occurring in trade and new strategic challenges. 2. Processes of co-operation among businesses. 3. Examples of businesses consolidation. The occurrence of consolidation among Polish businesses is intensifying, however the pace of these changes is not very fast. For example, among 95.5 thousand of grocery shops 66% remains un-unionized! The reasons for the above include: lack of complex legal solutions regulating the commerce area, limited possibilities of obtaining credit and means from the European Union, distrust of Polish merchants towards common activities (ventures).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 96-107